Analisis Penggunaan Variasi Bahasa Indonesia pada Akun Instagram Ria Ricis (@riaricis1795) - Qisthy Aufany Adrianto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the use of Indonesian language variations on Ria Ricis's Instagram account, a renowned influencer with a diverse audience. The analysis seeks to understand how Ria Ricis utilizes language variations as a communication tool, builds relationships with her followers, and shapes her self-image on social media. The research employs a qualitative approach by examining content such as captions and comments based on theories of language variation, pragmatics, and digital communication. The results show that Ria Ricis uses a casual, flexible, and relatable language style, incorporating slang, colloquial expressions, and popular terms. The language employed reflects an effective communication strategy to foster emotional closeness with her audience. Moreover, the social media context enables the use of informal language to create interactive and authentic relationships. This study highlights the significance of language variations in strengthening social connections and constructing personal identity on social media.